Kepercayaan Diri, Kematangan Emosi, Pola Asuh Orang Tua Demokratis dan Kenakalan Remaja - Fatchurahman, M. (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract, The aims of this study is to investigate the correlations among the self-confidence, emotional maturity and the democratic-parenting with the youth delinquency. The subjects of this study were 46 students of class X of SMK Muhammadiyah,Malang. Based on  the correlation and the regression analysis were obtained  there were no correlation among the  emotional maturity  variable and the democratic parenting  with the youth delinquency. Expectionally  the self-confidence, there was significant and negative correlation with youth delinquency. The more self confidence, the less youth delinquency. Keywords: Self-confidence, emotional maturity, democratic parenting, youth  delinquency.